Estrogen and progesterone receptors and the binding kinetics in human saphen and umbilical vein endothelial cells - (:unkn) unknown (My University, 1995)
Although it has been shown that estrogens and progesterones increase the risk of arterial and venous thrombosis in a dose related manner, the mechanism of their action has not yet been clarified. Effects of sex steroids may be due to their effects on endothelium which participates in regulation of hemostatic processes. In this study, cytosolic estrogen (ER), and progesterone receptors (PR) in human umbilical vein and saphen vein endothelial cells and cultured human umbilical vein endothelial cell (HU-VEC) were measured using the Abbott ER-EIA and PR-EA Monoclonal System, which is an enzyme immunoassay. Also characteristics of binding of estradiol to HUVEC receptors were examined by using radiolabeled hormones. Receptor content of nuclei of endothelial cells were also measured after fractionation. The distribution of ER between the cytoplasm and nucleus was found to be 50% each. No significant PR was detected in any of cell fractions used. The amount of cytosolic estrogen receptors measured by the immunological method was 6.06 ± 5.07 fmol/mg cytosol protein in HUVEC, 16 fmol/mg cytosol protein in cultured HUVEC and 4.2 fmol/mg cytosol protein in human saphen vein endothelial cells. Variations between male and females were insignificant (p > 0.05). Saturation binding analysis using 3H-17β-estradiol indicate the presence of cytosolic high affinity binding sites with an equilibrium dissociation constant K(d) = 0.43 x 10-10 M and B(max) of 23.9 fmol/mg cytosol protein for estradiol in HUVEC. The presence of receptors in endothelial cells suggest that these cells are potentially capable of responding to estrogens and endothelial function may be regulated by the hormone.
Keywords: binding kinetics; endothelium; estradiol receptors; progesterone receptors